Color in description purpose Ayyubid poetry (Journal of the College of Basic Education, 2022)
This study aims to highlight the aesthetics of employing color in the poetry of the Ayyubid poets. Color has an emotional or social function... gained from the context of the poetic text. Animal, and other things such as: weapons and wine.